Kesiapan Aktor dan Kebijakan dalam Mewujudkan Smart Mobility di Provinsi Bali - Purnama, Arif Ganda; Hutama, Surya Tri Esthi Wira; Wijaya, M. Indra Hadi; Pratami, Mentari (Bali Membangun Bali: Jurnal Bappeda Litbang, 2025)
Purpose: As the gateway to Indonesian tourism, Bali needs to transform into a smart city to overcome the complexity of the political environment, social and economic disparities, resolve rigid administrative systems, and increase the effectiveness of city infrastructure. One of the infrastructure problems is in the transportation sector which is caused by limited public transportation facilities to keep up with the increasing use of land as a generator and the use of private vehicles. This research tries to analyze the role of the actors and policies involved and the role of policy, power, interests, the relationship between actors and policies in realizing smart mobility. Research methods: Data sources for analysis were obtained from secondary data from planning documents and were verified through limited discussions with stakeholders. Results and discussion: The results obtained by policies related to smart mobility in Bali Province have fulfilled all the components that form smart mobility in Bali Province. Actors with high capabilities and interests include the Inna Group, Electric Vehicle Committee, Transportation Agency, PLN, and GIZ. The analysis of the relationship between policies, actors, and indicators of smart mobility shows that all actors and policies in Bali Province are suitable for realizing smart mobility. Implication: By recognizing smart mobility, it is hoped that people will get a better quality of life in several aspects: a better environment, better public services, and better economic and employment opportunities.